Raman spectroscopic investigations of natural jennite from Maroldsweisach, Bavaria, Germany. (29th December 2015) - Müller, Dirk; Hochleitner, Rupert; Fehr, Karl Thomas
Abstract : A full‐range pattern (100–3700 cm −1 ) analysis of natural jennite was performed for the first time by Raman spectroscopy, applying a polarized laser at a wavelength of 532 nm. A prominent structural feature of jennite is the preferred orientation of Si‐tetrahedron and Ca‐octahedron chains parallel [010]. The latter ones are additionally coupled to H2 O molecules and OH groups. This arrangement leads to a strong dependence on orientation for the intensity ratios of mainly three different regions in the Raman spectra: 180–210, 950–1050 and 3100–3650 cm −1 . These sections can be assigned to Ca–O lattice vibrations, Q 2 Si–tetrahedron stretching and O–H vibrations of H2 O molecules and Ca–OH structures, respectively. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A full‐range pattern (100–3700 cm −1 ) analysis of natural jennite was performed for the first time by Raman spectroscopy. A prominent structural feature of jennite is the preferred orientation of Si‐tetrahedron and Ca‐octahedron chains parallel [010]. The latter ones are additionally coupled to H2 O molecules and OH groups. This arrangement leads to a strong dependence on orientation of distinct regions in the Raman spectra, discussed herein.